Breaking the commute barrier: How women in Jabodetabek overcome daily challenges on commuting for work - Hidayati, Inayah (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
Ensuring safe and convenient transportation is vital for promoting gender equality. Unfortunately, women in Jabodetabek, Indonesia, frequently express insecurity in public transport due to harassment and violence, particularly in crowded buses and trains. This is a critical issue since secure and reliable transportation enables women to engage fully in education, employment, and daily activities.  To better understand women's experiences with public transportation in Jabodetabek, a study was conducted using a case study method. Six women commuters who used public transportation to travel within and between Jabodetabek were recruited based on their willingness to share their experiences and the diversity of their routes. The study used qualitative research methods to collect data, including in-depth interviews and observations of informants' commutes. The study discovered that women in Jabodetabek consider safety concerns and social norms crucial when deciding their transportation mode and route. Women's route choices are influenced by the presence of other women, well-lit areas, and visible security personnel, which contribute to their perceived safety and comfort. Gender plays a significant role in shaping these decisions. The implications of these findings are significant for transportation policy and planning in Jabodetabek. The research underscores the need to develop gender-responsive transportation policies and programs that address women commuters' unique challenges and needs. For example, transportation planners can take steps to increase security personnel presence and improve lighting in areas frequented by women. Moreover, providing women-only transportation options can enhance the safety and comfort of women during their travel. The present research is distinguished by its investigation of women's route choices and the multifaceted factors that shape their decision-making process. In addition, this research represents a gap in the existing literature that has yet to be extensively examined, thereby rendering this study a distinctive and valuable contribution to the field.